Risk based explanations of the equity premium - Donaldson, John B. 1948-; Mehra, Rajnish 1950- (National Bureau of Economic Research, 2007)
This essay reviews the family of models that seek to provide aggregate risk based explanations for the empirically observed equity premium. Theories based on non-expected utility preference structures, limited financial market participation, model uncertainty and the small probability of enormous losses are detailed. We impose the additional requirements that candidate models yield consistent inter temporal portfolio choice and that a representative agent can be constructed which is independent of the underlying heterogeneous economy's initial wealth distribution. While many models are able to replicate a wide variety of financial statistics including the premium, few satisfy these latter criteria as well.
Literaturverz. S. 90 - 101